Seasonal Variations of Aneurismal Subarachnoid Hemorrhage - Dey , Subash Kanti; Husain , Shakir; Bakshi , Lipy; Dey , Sukla; Bakshi, Mithun Kumar; Ahsan, Habib; Md Shahidullah , -; Barman , Kanoj Kumar; Rahman, Kazi Mohibur; Khan , Sharifuddin; Saha, Uttam Kumar (Bangladesh Journal of Neuroscience, 2013)
Background: Rupture of aneurysm is a vascular events, it is assumed that season exerts an influence in the incidence of rupture of aneurysm. But seasonal variation on the aneurismal subarachnoid hemorrhage (ASAH) is a subject of controversy. Some previous studies reported that changes in the biometric pressure in different season modulate the occurrence of vascular events. Aims: To evaluate the role of seasons of a year on the onset of aneurismal subarachnoid hemorrhage (ASAH). Methodology: This is a retrospective study. There were 377 patients with definite diagnosis of ASAH. Patients were evaluated in two age groups of >60 and less than 60. Results: The frequency of ASAH in winter and autumn was 55.4% and spring and summer was 44.6%% respectively. This difference was statistically significant (p>o.o5). The effect of hypertension and diabetes mellitus revealed no influence on subarachnoid hemorrhage (SAH) in our study. Conclusion: There was influence of seasonal variation on the onset of ASAH and which was predominantly during winter and autumn. Bangladesh Journal of Neuroscience 2013; Vol. 29 (1) : 15-17